المقريزي خلدوني يكتب عن الخطط والملوك - عبد الغني عبد الله, يسري (جامعة الوادي University of Eloued, 2016)
ما زلنا في حاجة ماسة لتفعيل البحث المقارن في عصور التاريخ ، لأنه ميدان يساعدنا على استجلاء الأسس العامة في الحضارة الإنسانية ، والقرن الخامس عشر الميلادي الموافق التاسع الهجري تقريبًا ، من أهم العصور بسبب ما بدا فيه من عناصر توجيهية وأحداث مؤذنة بتغير أحوال الدول والجماعات بالشرق والغرب . إن قصة المؤرخين في مصر خلال القرن المشار إليه لا يمكن أن تتم إلا بذكر العلامة / ابن خلدون والإشارة إلى فضله الكبير ، وإلى تلاميذه الذين نهلوا من منهجه وعلمه ، وقد أخذنا أول تلاميذه ، ونعني به المؤرخ المصري / أحمد بن علي المقريزي ، حاولنا أن نعرف به ، ونلقي الضوء الكاشف على رحلة حياته ، وأهم مؤلفاته التاريخية ، وأسلوبه في التأليف ، وأخلاقياته ، ورأي معاصريه فيه ، ذلك بالإضافة إلى الوقوف على تأثره بفكر ابن خلدون فيما كتبه من آراء وأفكار وتحليلات ورؤى تاريخية ، فلعلنا نكون قد وفقنا إلى ذلك . We are still in dire need to activate comparative research in periods of history, because the field will help us to elucidate general principles in human civilization, and the Horn of the fifth century AD, corresponding to almost the ninth AH, of the most important times because of what appeared to be its guiding elements and events marking the change conditions of countries and groups in the Middle and West. The story of historians in Egypt during the mentioned century can only be done by mentioning the brand / Ibn Khaldun and the reference to the great virtues, and to his disciples who are energized by his approach and his knowledge, have taken the first disciples, and we mean of Egyptian / Ahmed Bin Ali Maqrizi, we tried to know it, and take a light detector on the journey of his life, and the most important historical writings, and his style of writing, and ethics, and the opinion of his contemporaries in which, in addition to stand on influenced by the ideas of Ibn Khaldun in his books of opinions and ideas and analyzes and visions of a historic, Let us we have been successful at it.
Keywords: المقريزي - الخطط والملوك